Primary Cerebral Hemangiosarcoma in an Adult Labrador Retriever Dog - Stern, Adam W. (Brazilian Journal of Veterinary Pathology, 2014)
A 6-year-old, castrated male, Labrador Retriever dog presented to the referring veterinarian for acute onset of lethargy. Clinical examination revealed hyperesthesia of the face and blindness in the right eye. The animal died in the hospital and was submitted for postmortem examination. At postmortem examination, a dark red mass (2.0 cm x 1.8 cm x 1.6 cm) had infiltrated the right frontal lobe of the cerebrum. Microscopically, the tumor was composed of small caliber vascular channels lined by neoplastic endothelial cells. Immunohistochemical staining revealed widespread expression of CD31 and the absence of pan-cytokeratin expression in neoplastic cells. The diagnosis of primary cerebral hemangiosarcoma was made. The brain is a rare primary site for hemangiosarcoma in the dog.